Elements of the economic intelligence of the organization and its role in achieving economic growth: Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of the research is to demonstrate of the relation and the influence of the components of economic intelligence (strategic alertness, information security policy, impact policy) in achieving of economic growth (creativity, competitiveness, quality improvement). The questionnaire was used as a main tool for selected sample. Answers analyzed by using the statistical program (SPSS)  to calculate the arithmetic mean, standard deviation, weight percentage, correlation, F test, and Squared factor (R2). The research derived its importance from the distinguished role of information systems in the work of industrial companies, and its impact toward achieving economic growth rates in its various activities. The research demonstrated some results, the most important were:• The policy influence has been taken the first rank among economic intelligence elements, followed by strategic vigilance and then information security policy.• The competitiveness has been taken the first rank among economic growth, followed by quality improvement and then creativity.• The test results demonstrated positive relation between economic intelligence elements and economic growth in (33%).Therefore, allocating of budgets and encouraging of research and development in order to support creativity and improve the quality of production consider by company management the most important recommendations in this research.